Denosumab in advanced/unresectable giant-cell tumour of bone (GCTB): For how long?. (May 2017) - Palmerini, E.; Chawla, N.S.; Ferrari, S.; Sudan, M.; Picci, P.; Marchesi, E.; Leopardi, M. Piccinni; Syed, I.; Sankhala, K.K.; Parthasarathy, P.; Mendanha, W.E.; Pierini, M.; et al.
Abstract: Background: Giant-cell tumours of bone (GCTB) are RANK/RANK-ligand (RANKL) positive, aggressive and progressive osteolytic tumours. Denosumab, a RANKL inhibitor, was FDA-approved for adults and skeletally mature adolescents with unresectable GCTB or when surgical resection is likely to result in severe morbidity. Data on long-term toxicity and activity of denosumab monthly 'GCTB-schedule' (120 mg per 12/year, 1440 mg total dose/year) are lacking. Methods: Patients with GCTB receiving denosumab, 120 mg on days 1, 8, 15, 29 and every 4 weeks thereafter, from 2006 to 2015 treated in two centres were included. Long-term toxicity was evaluated. Results: Ninety-seven patients were identified. 43 patients underwent resection of the tumour with a median time on denosumab treatment of 12 months (range 6–45 months). Fifty-four patients had unresectable GCTB's (male/female 23/31, median age 35 years [range: 13–76 years], 26% presented with lung metastases, 31% had primary tumor located to the spine, 63% were relapsed after previous surgery) with a median time on denosumab of 54 months (9–115 months). In the unresectable GCTB group, tumour control and clinical benefits were observed in all patients undergoing denosumab, whereas 40% of patients discontinuing denosumab had tumour progression after a median of 8 months (range 7–15 months). Adverse events: Overall, six (6%) patients developed osteonecrosis of jaw (ONJ): 1/43 (2%) in the resectable group, 5/54 (9%) in the unresectable group, with a 5-year ONJ-free survival of 92% (95% CI 84–100). Only patients with prolonged treatment experienced mild peripheral neuropathy (6/54, 11%), skin rash (5/54, 9%), hypophosphataemia (2/54, 4%) and atypical femoral fracture (2/54, 4%). Conclusions: Prolonged treatment with denosumab has sustained activity in GCTB, with a mild toxicity profile. The dose-dependent toxicity observed recommends a careful and strict monitoring of patients who need prolonged treatment. Decreased dose-intensity schedules should be further explored in unresectable GCTB. Highlights: No data on long term denosumab in GCTB available. We report on 54 patients receiving denosumab for a median of 4 years. All patients had tumor control while on denosumab. ONJ risk was documented in 9% of patients and it was dose-dependent. Fourty percent of patients discontinuing denosumab had tumor progression after a median of 8 months.